2020
DOI: 10.1016/j.addma.2020.101289
|View full text |Cite
|
Sign up to set email alerts
|

Functionalizing magnet additive manufacturing with in-situ magnetic field source

Abstract: Additive manufacturing via 3-D printing technologies have become a frontier in materials research, including its application in the development and recycling of permanent magnets. This work addresses the opportunity to integrate magnetic field sources into 3-D printing process in order to enable printing, alignment of anisotropic permanent magnets or magnetizing of magnetic filler materials, without requiring further processing. A non-axisymmetric electromagnet-type field source architecture was designed, mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…The bar graphs indicate the efficacy of field structuring to achieve higher magnetic properties, i.e., saturation, remanence, and coercivity for the in-plane direction are consistently higher for samples S2 and S3 compared to the isotropic sample S4. Present observations are congruent to magnetic composites containing field structured particles in a thermoplastic matrix [ 31 , 32 ]. Overall, the present study validates the effectiveness of field structuring magnetic particles in thermoset polymers using a permanent magnet array, enabling an efficient fabrication of anisotropic magnetic composites for a variety of applications in electrical and electronic devices.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The bar graphs indicate the efficacy of field structuring to achieve higher magnetic properties, i.e., saturation, remanence, and coercivity for the in-plane direction are consistently higher for samples S2 and S3 compared to the isotropic sample S4. Present observations are congruent to magnetic composites containing field structured particles in a thermoplastic matrix [ 31 , 32 ]. Overall, the present study validates the effectiveness of field structuring magnetic particles in thermoset polymers using a permanent magnet array, enabling an efficient fabrication of anisotropic magnetic composites for a variety of applications in electrical and electronic devices.…”
Section: Resultssupporting
confidence: 83%
“…In-situ magnetic alignment using an electromagnet integrated with fused deposition modelling equipment was tested on anisotropic NdFeB/samarium ferrite nitride powders reinforcing a Nylon 12 matrix. It was found that the degree of alignment was a function of applied magnetic field and printing temperature [ 32 ]. It was additionally noted that alignment studies were primarily conducted in thermoplastic polymer-bonded permanent magnets.…”
Section: Introductionmentioning
confidence: 99%
“…Big area additive manufacturing (BAAM) is a system developed by Cincinnati Inc. to fabricate large parts via a material extrusion method which has produced bonded Nd-Fe-B magnets with attractive properties. [16][17][18][19][20][21][22] BAAM deposits layers of molten thermoplastics with magnet particles by extruding the material through a nozzle. The thermoplastic solidifies rapidly after deposition, allowing a large magnet to be built quickly.…”
Section: D Printing Of Bonded Magnet Via Binder-jet and Extrusionmentioning
confidence: 99%
“…Electromagnetism principles and magnetic actuators have been implemented in various applications such as metal forming, where a solenoid with 15 turns generates a magnetic force to push a light metal in order to form a cellphone case [1], real-time production of magnetic materials with the 3D printer in additive manufacturing is feasible by aligning the particles with the magnetic field [2]. In addition, magnetic levitation can be used to design a stable suspension for metal additive manufacturing, which results in substrate elimination [3].…”
Section: Introductionmentioning
confidence: 99%